The impact of facebook marketing on customer purchase intention in mid-scale restaurants: a study in Gujranwala, Pakistan / Nurul Firdaus Sikandar Hayat, Nurnajihah Ahmad Kamal and Tajulurrus Mohammad - Sikandar Hayat, Nurul Firdaus; Ahmad Kamal, Nurnajihah; Mohammad, Tajulurrus (Universiti Teknologi MARA, Terengganu, 2024)
This study focuses on the development and implementation of a research instrument designed to assess customer responses to Facebook advertisements for midscale restaurants in Pakistan, utilizing a sample size of 165 respondents. Facebook marketing has proven to be a powerful tool in influencing customer purchase intentions, making it essential for restaurants. Emphasizing a high response rate and data quality, the instrument's design prioritized questionnaire length, question structure, and overall clarity. A trained research assistant distributed the questionnaire, facilitating effective communication and addressing respondents' inquiries. The survey was disseminated through community platforms such as WhatsApp and Facebook groups, accompanied by an ethics notice to ensure confidentiality. Participation was restricted to individuals who had previously seen the selected restaurant’s Facebook advertisement, enhancing data relevance. The questionnaire was crafted to be straightforward, minimizing cognitive demands on respondents, and was available in both English and Urdu to accommodate diverse language proficiencies. The instrument included adapted items from prior studies and was organized into five sections aligned with the study's objectives: to identify the factors that influence customer purchase intention toward Facebook advertisements for midscale restaurants in Gujranwala and to examine the most significant factors driving this intention. A five-point Likert scale was employed to measure respondents' levels of agreement, providing nuanced insights into customer attitudes and purchase intentions related to social media advertising. Correlation analysis revealed significant relationships among the variables of information, price, feedback, and purchase intention, with information showing the strongest relationship with purchase intention (r = .563, p < .001). Price and feedback also demonstrated substantial correlations with purchase intention, further supporting the notion that these factors significantly influence consumer behavior in the context of social media advertising. Overall, this research instrument serves as a valuable tool for understanding how Facebook advertisements impact customer perceptions and intentions in Pakistan, providing restaurateurs with actionable insights for improving their marketing strategies in a competitive landscape.